Assessment of frailty in geriatric patients admitted to oncology: a quality improvement project - Safiyyah Samad; Robert Brown (Future Healthcare Journal)
Introduction: Frailty is known to have significant impacts on hospital outcomes, including length of stay, readmission frequency and mortality.1Guidance from NHS England and the British Geriatric Society (BGS) states that all patients over 65 should have frailty assessed with the Clinical Frailty Scale (CFS) on arrival to hospital, for both elective and emergency admissions.2Accurate frailty assessment provides a broad overview of the complexity of a patient and directs to appropriate management, including comprehensive geriatric assessment (CGA). NHS England and BGS guidance recommends that all patients with a CFS of 6 or above should have a CGA as soon as possible by a team with expertise in frailty.2 Evidence suggests improved outcomes for older adults who undergo a CGA during admission.3However, despite its importance, frailty is inconsistently assessed or inaccurately recorded in many clinical settings. This project aimed to improve the assessment of frailty in patients aged 65 and above admitted to the oncology department using the CFS. Method: We reviewed data for patients aged 65 and over admitted to the oncology department, including elective and emergency admissions. We assessed the proportion of patients admitted from 1 to 31 July 2024 who had a documented frailty score within 48 h of admission to evaluate existing concordance with guidance.We developed and delivered a frailty teaching session to the oncology team to improve understanding of the need for accurate frailty assessment. The aim was to increase the proportion of patients having frailty assessments conducted at admission.We evaluated the efficacy of this intervention by reviewing documented frailty scores for admissions from 8 January 2025 to 8 February 2025. Results: 155 patients were admitted to oncology between 1 and 31 July 2024 (pre-intervention). 31% (n=48) of these patients were aged 65 and over. Only 2% (n=1) of these patients had a frailty score documented within 48 h of admission.123 patients were admitted to oncology between 8 January and 8 February 2025 (post-intervention). 30% (n=37) of these patients were aged 65 and over. 19% (n=7) of these patients had a frailty score documented within 48 h of admission. Discussion: Our initial results showed poor adherence to national guidance for completing frailty assessments in the over 65s, with only 2% of those over age 65 being assessed with a frailty score.Following our intervention, adherence to frailty assessment guidance improved to 19% of suitable patients being assessed. This intervention was low intensity as the teaching session was integrated into existing teaching schedules, requiring no additional resources. Conclusions: Our findings demonstrate a gap in the documentation of frailty assessments for older patients admitted to oncology. Despite a significant improvement in frailty assessments following our intervention, overall assessment numbers remained low.This gap highlights the need for education to enhance understanding and adherence to frailty assessment guidelines. Low-intensity educational interventions may be an effective way to improve implementation of frailty assessments.Our quality improvement did not assess for adherence to further guidance following frailty assessment. Further work could include targeting improvement towards CGA implementation.